An efficient multiplier by pass transistor logic partial product and a modified hybrid full adder for image processing applications. (December 2021) - Rafiee, Mahmood; Pesaran, Farshad; Sadeghi, Ayoub; Shiri, Nabiollah
Abstract: Different digital multipliers have resulted from various algorithms and hardware designs. This article presents a high-performance multiplier by a novel AND gate and a modified hybrid full adder (FA) cell. The AND is designed by using the pass transistor logic (PTL) technique and a speed-up transistor, while the FA is based on the transmission gate (TG). Low-power, high-speed, low power-delay-product (PDP), and high competency of both circuits for using in sophisticated structures like multipliers are confirmed by mathematical relations. The proposed 4-bit array multiplier circuit along with the pad has a 2.87 mm 2 total area and is investigated under different circumstances including VDD, frequency, load capacitances, and process-voltage-temperature (PVT) variations using Monte Carlo method (MCM) by HSPICE tool and 90 nm technology. The efficiency of the multiplier in image processing applications is proved with average improvements of 12.61% and 32.045% for peak signal-to-noise ratio (PSNR) and PDP compared to state-of-the-art designs, respectively. The overall results of the multiplier approve its capability for digital signal processors (DSPs).